2019
DOI: 10.1002/ygh2.373
|View full text |Cite
|
Sign up to set email alerts
|

The effects of proactive therapeutic drug monitoring vs reactive therapeutic drug monitoring in a virtual biologic clinic, a retrospective cohort study

Abstract: Summary Background Proactive therapeutic drug monitoring (proactive‐TDM) to optimise maintenance infliximab (IFX) trough levels prior to loss of response reduces the risk of treatment failure, inflammatory bowel disease (IBD)‐related surgery and hospitalisation when compared with reactive monitoring (reactive‐TDM). Aim The aim of this study is to investigate if proactive‐TDM in a virtual biologic clinic (VBC) improves patient disease control determined by number of hospital admissions, surgeries, patient repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Nine were RCTs 17,19,20,[29][30][31][32][33][34] and the remaining were cohort studies. There were four prospective cohort studies, [35][36][37][38] 11 retrospective cohort studies [6][7][8]18,27,[39][40][41][42][43][44] and two that were both prospective and retrospective cohort studies. 5,45 Table 1 shows a summary of the studies.…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine were RCTs 17,19,20,[29][30][31][32][33][34] and the remaining were cohort studies. There were four prospective cohort studies, [35][36][37][38] 11 retrospective cohort studies [6][7][8]18,27,[39][40][41][42][43][44] and two that were both prospective and retrospective cohort studies. 5,45 Table 1 shows a summary of the studies.…”
Section: Re Sultsmentioning
confidence: 99%
“…Four studies were eligible for the proactive vs reactive arm, with 352 patients in the proactive TDM arm and 368 in the reactive TDM arm 6,7,36,39 . Proactive TDM was associated with a significant risk reduction in hospitalisation (RR 0.33, 95% CI 0.21-0.54, p<0.01, 9).…”
Section: Effects Of Therapeutic Drug Monitoring On Hospitalisationmentioning
confidence: 99%
“…However, hard evidence that this strategy actually works is hard to find. In the case of anti‐TNFs, there is now very good evidence that therapeutic drug monitoring (TDM) greatly assists the physician in selecting the appropriate dosing for the patient 2 . TDM for vedolizumab is not widely available and its efficacy and utility in managing the patient with loss of response is not well established yet.…”
mentioning
confidence: 99%
“…It may seem to be self‐fulfilling prophecy that by proactively monitoring drug levels and antibodies in biological therapy, physicians can achieve better disease control . However, even the most obvious treatment propositions need to be demonstrated by a prospective study.…”
mentioning
confidence: 99%
“…In the previous issue of GastroHep, Tun et al demonstrated that there is a high prevalence of positive antibodies to infliximab (ATI) post‐induction and is associated with a high rate of rapid treatment failure . In this issue, McGettigan et al conducted a prospective cohort study following the clinical course of two groups of patients, one with reactive monitoring and the other with proactive drug monitoring …”
mentioning
confidence: 99%